12
$\begingroup$

I'm trying to understand what the relation is between the direct product and the quotient group.

If we let $H$ be a normal subgroup of a group $G$, then it is not too difficult to show that the set of all cosets of $H$ in $G$ forms a quotient group $G/H$: \begin{equation} G/H = \{ g H \mid g \in G \} \end{equation}

On the other hand, the Cartesian product of two groups $G$ and $H$ is defined as: \begin{equation} G \times H = \{ (g,h) \mid g \in G \text{ and } h \in H \} \end{equation} where $(g,h)$ denotes the set of ordered pairs. The direct product operation on this set is defined as: \begin{equation} (g_1,h_1)(g_2,h_2) = (g_1g_2,h_1h_2) \in G \times H \end{equation} and it is easy to see that the direct product forms a group.

Is the following statement true: \begin{equation} K = G \times H \implies G \simeq K / (\{e_G \} \times H) \end{equation} If so, under what conditions is it true? And how can we see it is true (or false)?

Edit 26/03:

Up to this point, I believe I have found a method (see below) of showing the isomorphism relation. I would be really grateful if someone could tell me whether this proof is correct or not.

Let us identity the elements of $h \in H$ with element of $K$ by setting $h \equiv (e_G,h)$. The elements of $K/H$ are as usual defined by: \begin{equation} K/H = \{ (g,h) H \mid g \in G \text{ and } h \in H \} \end{equation} Since $h_1H=H$ for some $h_1 \in H$, we have: \begin{equation} (g,h)H = (g',h')H \iff g=g' \text{ and } h' = h h_1 \tag{1} \end{equation} and so without loss of generality we can write every element of $K/H$ in the form $(g,e_H)H$. Now, let the map: \begin{equation} f : G \to K/H \end{equation} be defined by: \begin{equation} f(g) = (g,e_H) H \tag{2} \end{equation} The map is one-to-one. This can be seen by equation $(1)$, because if: \begin{equation} f(g) = f(g') \end{equation} then: \begin{equation} (g,e_H) H = (g',e_H) H \implies g=g' \end{equation} Furthermore, the map is trivially onto: \begin{equation} \forall (g,h) H \in K/H \; \exists \; g \in G \; , \; f(g)=(g,h) H \end{equation} and thus the map is bijective. Finally, the map is also a homomorphism, because: \begin{equation} f(gg') = (gg',e_H) H = (g,e_H)(g',e_H) H = (g,e_H)(g',e_H) HH = (g,e_H) H (g',e_H) H = f(g) f(g') \end{equation} and so $f$ is a isomorphism. Thus, by definition of equation $(2)$, we have shown that $G \simeq K/H$.

Any input is much appreciated.

$\endgroup$
  • 1
    $\begingroup$ Note that $H$ isn't even a subgroup of $G\times H$ strictly speaking. What you want to show is $G \cong K\big/ \left(\{e_G\}\times H\right)$. $\endgroup$ – Christoph Mar 23 '14 at 19:56
  • $\begingroup$ @Christoph thanks, I've updated my question. $\endgroup$ – Hunter Mar 23 '14 at 20:02
8
+100
$\begingroup$

Your solution is not wrong but it has unnecassary steps. You can simply use following arguments.

Let $\pi:G\times H\to G$ be projection map .i.e. $\pi(g,h)=g$. It is clear that map is onto.

Claim$1:$ $\pi$ is an homomorphism;

$$\pi((g_1,h_1)(g_2,h_2))=\pi((g_1g_2,h_1h_2))=g_1g_2=\pi((g_1,h_1))\pi((g_2,h_2))$$ and since it is onto map it is an epimorphism.

Claim$2$: $Ker(\pi)=e_G\times H$

Let $\pi(x,y)=e_g$ then you can say that $x=e_g$ and $y$ is any element in $H$ so result follows. By the way it also show that $e_G\times H$ is normal in $G\times H$.

Result: By first isomorphim theorem; $$(G\times H)/ker(\pi)=(G\times H)/(e_G\times H)\cong G$$

Notes: By using the other projection you can show smiliar argument for $G\times e_H$ and $H$. I hope you are familiar with isomorphism theorems.

$\endgroup$
  • $\begingroup$ Thanks for your reply! No, I am not familiar with isomorphism theorems, but I'm always willing to learn. However, this is why I wanted to be sure that my "proof" is correct. $\endgroup$ – Hunter Mar 28 '14 at 20:19
  • $\begingroup$ I'm not sure how it works now: I want to get as much attention as possible to this question, in order to see if anybody can find a mistake. But if by the end of the 7 day period (5 days left) no one has found one, then I want to give the bounty to you for confirming my proof. $\endgroup$ – Hunter Mar 28 '14 at 20:21
  • 1
    $\begingroup$ @Hunter: Actually, your proof includes it that is why your solution is long; first isomorphism theorem says that $\phi:G\to H$ is a epimorphim then $G/ker(\phi)\cong H$. I suggest you to learn all isomorphism theorems: en.wikipedia.org/wiki/Isomorphism_theorem $\endgroup$ – mesel Mar 28 '14 at 20:29
  • 1
    $\begingroup$ @Hunter: people.reed.edu/~jerry/332/09isom.pdf this source seems to good. $\endgroup$ – mesel Mar 28 '14 at 20:35
3
$\begingroup$

This statement is always true, since $H$ is a normal subgroup of $G \times H$ (i.e. $xH = Hx$ for all $x \in K$). To see why, consider two cases:

  1. The case $x \in H$

  2. The case $x \notin H$

Then, the statement follows from the fundamental theorem of homomorphisms. By the way, you should replace the second $=$ sign by the $\simeq$ sign, in your statement.

$\endgroup$
  • $\begingroup$ Thanks for your reply. I understand that $(e_G,H)$ is a normal subgroup of $G \times H$ and that $(e_G,H)$ is isomorphic to $H$, but I don't see why that would make the statement true. Can you elaborate? $\endgroup$ – Hunter Mar 23 '14 at 19:32
  • $\begingroup$ I have tried to answer the question myself and would be really interested to have feedback from you if you have time. $\endgroup$ – Hunter Mar 24 '14 at 16:28
2
$\begingroup$

Suppose $G=H\times K$. We want to show $G/K\simeq H$. Consider the map $H\times K\to H\times 0\simeq H$ given by $(h,k)\to (h,0)$. What is the kernel of this? What is it's image?

In general, the whole point of the direct product is given groups $H$ and $K$ to form a group $G=H\times K$ with copies $\hat K=1\times K$ and $\hat H=H\times 1$ such that

$(\rm i)$ $\hat H,\hat K\lhd G$

$(\rm ii)$ $G=\hat H\hat K$

$(\rm iii)$ $\hat K\cap \hat H=1$

Moreover, $G/\hat K\simeq H$ and $G/\hat H\simeq K$.

Conversely, if $G$ contains subgroups $H,K$ with $H,K\lhd G$, $H\cap K=1$ and $HK=G$, then $G\simeq H\times K$.

$\endgroup$
  • 2
    $\begingroup$ Shouldn't we look at $G\times H\to G$ to obtain the desired isomorphism? $\endgroup$ – Christoph Mar 23 '14 at 19:50
  • $\begingroup$ @Christoph I usually write $H\times K=G$, so I slightly skipped over the OPs notation. $\endgroup$ – Pedro Tamaroff Mar 23 '14 at 19:56
  • $\begingroup$ So are we looking for: $$\mathrm{Ker} = \{h \in H \text{ and } k \in K \mid f((h,k)) =(h,e_K) \}$$ where $f$ is a homomorphic function? If so, if have no idea what this information tells us. (I'm sorry, I'm studying physics and not mathematics.) $\endgroup$ – Hunter Mar 23 '14 at 19:58
  • $\begingroup$ @PedroTamaroff I have tried to answer the question myself and would be really interested to have feedback from you if you have time. $\endgroup$ – Hunter Mar 24 '14 at 16:28
  • $\begingroup$ @Hunter I don't understand what you're asking. $\endgroup$ – Pedro Tamaroff Mar 24 '14 at 16:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.